AN ANALYSIS OF ONLINE ASSESSMENT IN TEACHING ENGLISH - Wibowo, Furqon Edi; Novitasari, Umi (IKIP Siliwangi, 2021)
This study aimed to identify kinds of online assessment implemented by English teachers and to analyze the students‘perception of using online assessment in Tenth Grade of SMA Muhammadiyah 2 Surakarta in Academic Year 2019/2020. The researcher collected the data by questionnaire, interview, and documentation. The researcher used technique of analyzing the data by Miles and Huberman which have three phases. They are Data Reduction, Data Display, and Drawing Conclusion. For the trustworthiness of the data, the researcher used Methodological Triangulation. The result indicated that all English teachers have implemented variative online assessment through Google Form, Google Classroom, Edmodo, Quizzes, and Instagram. There are advantages, disadvantages, challenges face by the teacher applied online assessment such as designing the right assessment, controling the student in online, and got bad internet connection. Meanwhile, the students have positive and negative perception toward the implementation of online assessment. The positive perception showed that the student enjoyed the online assessment, obtained feedback immediately, flexible, time saving, effective, and more confident in doing online assessment. However, the student also had negative perception such as need internet data, less motivation, unfocussed, cheating, and need a longer time. Keywords: Online Assessment, Kinds of Online Assessment, Students’ Perception